2021
DOI: 10.1115/1.4050935
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Numerical Study of Entropy Generation in Magneto-Convective Viscoelastic Biofluid Flow Through Poro-Elastic Media With Thermal Radiation and Buoyancy Effects

Abstract: Electromagnetic high-temperature therapy is popular in medical engineering treatments for various diseases include tissue damage ablation repair, hyperthermia and oncological illness diagnosis. The simulation of transport phenomena in such applications requires multi-physical models featuring magnetohydrodynamics, biorheology, heat transfer and deformable porous media. Motivated by investigating the fluid dynamics and thermodynamic optimization of such processes, in the present article a mathematical model is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 179 publications
0
2
0
Order By: Relevance
“…( ) A change in the amount of entropy in the flow of nanofluids is predicted. As there are also certain variations in thermal transport, it is possible to describe the total entropy [34][35][36][37] as follows:…”
Section: Densitymentioning
confidence: 99%
“…( ) A change in the amount of entropy in the flow of nanofluids is predicted. As there are also certain variations in thermal transport, it is possible to describe the total entropy [34][35][36][37] as follows:…”
Section: Densitymentioning
confidence: 99%
“…These phenomena can also be exploited in medical engineering applications which include cardiovascular flow control [28], MHD based biomedical micro‐pumps, micro‐bio‐mixers, blood cell manipulation (owing to haemoglobin content) [29], magnetohydrodynamic (MHD) microfluidic platforms for cell switching [30], magneto‐robotic endoscopy [31], electrocardiogram interaction with MHD [32], cardiac cycle synchronization of magnetic resonance imaging (MRI). Recent studies in computational simulations of magnetohydrodynamic medical flows have also examined a wide spectrum of applications including magneto‐micro‐robotic propulsion for embryological treatment [34], biomagnetic therapy [35], gastric endoscopy [36], bio‐inspired nanofluid smart micro‐pumps [37] and radiation tissue electromagnetic treatments [38]. These studies have confirmed that magnetic effects offer significant benefits in biomedical systems and have the advantage of being non‐intrusive and relatively easy to implement [39].…”
Section: Introductionmentioning
confidence: 99%